2013
DOI: 10.3402/gha.v6i0.21682
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with attrition, mortality, and loss to follow up after antiretroviral therapy initiation: data from an HIV cohort study in India

Abstract: BackgroundStudies from sub-Saharan Africa have shown high incidence of attrition due to mortality or loss to follow-up (LTFU) after initiating antiretroviral therapy (ART). India is the third largest country in the world in terms of HIV infected people, but predictors of attrition after ART initiation are not well known.DesignWe describe factors associated with attrition, mortality, and LTFU in 3,159 HIV infected patients who initiated ART between 1 January 2007 and 4 November 2011 in an HIV cohort study in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
81
7
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 26 publications
26
81
7
3
Order By: Relevance
“…36 However, our findings that individuals with higher CD4 counts were more likely to be LTFU is consistent with some reports 36,51 but not with others. [52][53][54] A similar study from Nigeria 25 found an increased risk of LTFU in patients with low (<100) and high (>350) CD4 counts, which the authors attributed to patients being dead, or believing themselves to be healthy and therefore not needing to return for care.…”
Section: H Aliyu Et Almentioning
confidence: 99%
“…36 However, our findings that individuals with higher CD4 counts were more likely to be LTFU is consistent with some reports 36,51 but not with others. [52][53][54] A similar study from Nigeria 25 found an increased risk of LTFU in patients with low (<100) and high (>350) CD4 counts, which the authors attributed to patients being dead, or believing themselves to be healthy and therefore not needing to return for care.…”
Section: H Aliyu Et Almentioning
confidence: 99%
“…It is known that compliance among patients who improve is poor compared with those who are still unwell while cultural practices may also play a role. [18,19] It is tempting to suggest that because the children in the sequential group felt much better than their counterparts in the conventional group, they failed to come for their follow-up visit.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Similar studies from different parts of India have reported tuberculosis to be the most important cause of mortality [20][21][22][23]. In a study from South Africa, presence of cryptococcal meningitis or oral candidiasis was an important predictor of mortality [24].…”
Section: Discussionmentioning
confidence: 87%